Prevalence of Scoliosis in Standard 6 Female Primary School Students in Marang District, Terengganu - Myat Moe, Thwe Aung; Kyin, Htwe; Ahmad Tajuddin, Abdullah (2013)
To determine the prevalence and associated risk factors of scoliosis, a cross-sectional study was conducted by using scoliometer, weighing machine and measuring tape. A structured questionnaire was given to 1001 standard 6 female students in 29 primary schools in Marang, Terengganu, Malaysia. Scoliosis screening was done by measuring Angle of Trunk Rotation (ATR) with scoliometer in 832 respondents from February to May 2013. Majority were Malay (98.8%) and 99.4% were 12 years old. Only 1% had family history. Prevalence of scoliosis identified by ATR ≥7˚ on screening was 2.0% and confirmed by Cobb’s angle in standing radiograph ≥10˚was 0.60%. ATR and age distribution, ethnics group and family history of scoliosis were not statistically correlated due to gross unequal distribution of variables. Only 32.6 % of students had menarche that was not correlated with ATR and Cobb’s angle. Weight and height was statistically correlated with ATR readings but not with Cobb’s angle. Girls in age of 12 years still have growth potential and risk of curve progression. Further observation is needed in students with Cobb’s angle ≤10˚and ATR 5-6˚ group. Scoliometer is a reliable screening tool because of significant correlation between ATR and Cobb’s angle statistically. Scoliosis screening with scoliometer is recommended to implement in School Health Services for early detection of scoliosis before progression of curve in high risked standard 6 female primary school students.